Genetic autonomy and low singlet oxygen yield support kleptoplast functionality in photosynthetic sea slugs - Havurinne Vesa; Handric Maria; Antinluoma Mikko; Khorobrykh Sergey; Gould Sven B; Tyystjärvi Esa (Oxford University Press, 2022)
The kleptoplastic sea slug Elysia chlorotica consumes Vaucheria litorea, stealing its plastids, which then photosynthesize inside the animal cells for months. We investigated the properties of V. litorea plastids to understand how they withstand the rigors of photosynthesis in isolation. Transcription of specific genes in laboratory-isolated V. litorea plastids was monitored for 7 days. The involvement of plastid-encoded FtsH, a key plastid maintenance protease, in recovery from photoinhibition in V. litorea was estimated in cycloheximide-treated cells. In vitro comparison of V. litorea and spinach thylakoids was applied to investigate reactive oxygen species formation in V. litorea. In comparison to other tested genes, the transcripts of ftsH and translation elongation factor EF-Tu (tufA) decreased slowly in isolated V. litorea plastids. Higher levels of FtsH were also evident in cycloheximide-treated cells during recovery from photoinhibition. Charge recombination in PSII of V. litorea was found to be fine-tuned to produce only small quantities of singlet oxygen, and the plastids also contained reactive oxygen species-protective compounds. Our results support the view that the genetic characteristics of the plastids are crucial in creating a photosynthetic sea slug. The plastid’s autonomous repair machinery is likely enhanced by low singlet oxygen production and elevated expression of FtsH.